Electrical alternans of TU wave in Romano-Ward syndrome. Issue 7 (July 1976) - Hiejima, K; Sano, T
Abstract : A case is presented in which an exceptional electrical alternans of the TU wave occurred in association with the Romano-Ward syndrome. This appears to be the first reported example of this association. Ventricular fibrillation was documented during the syncopal attacks. There was no evidence of abnormality of the serum electrolytes.